The Habitus for Keeping Gajah Wong River Clean: A Study of Islamic Ecofeminism - Riska Dwi Agustin (IAIN TERNATE, 2022)
This paper attempts to discuss the equality between women and men under the concept of humanity based on religious texts in preserving environment. All of human being have equal responsibility to tackle ecological crisis, extreme weather, global warming and disaster-risks. This paper would generate a fair understanding either women or men to bring together as a environment keeper. The author describes that the society have their own wisdom to interact with the environment in their activities. Habitus theory elaborates how the habit of humans can preserve the good exertion for natural conservation. Islamic ecofeminism specifically proliferates protection of biological matters and gender based-perspective in disaster-prone area.